Facebook used as a recruiting tool - Hooker, Laura; Rathke, Brandon (My University, 2011)
Social media is becoming increasingly integrated in the hiring process as companies choose their employees from widening pools of applicants. Past studies revealed that it is important for job seekers to recognize the effect of an unprofessional social profile on their job prospects. This study examines the impact of unprofessional Facebook profiles and gender of the applicant on the likelihood of being hired. Each participant was presented with one of four hiring packets and questionnaires to see if they would hire the applicant for a human resource generalist position. Results indicate that there is not a significant correlation between having a professional or unprofessional Facebook profile and the likelihood of being hired according to gender. However, there was a significant effect of having a professional or unprofessional profile and being hired for the job regardless of gender.
Keywords: Job hunting; Facebook (Firm); Online social networks; Employees--Recruiting